Severe ARDS Secondary to Pneumonia Requiring VV ECMO in the Setting of Newly Diagnosed Hairy Cell Leukemia - Daniel Gorman DO, MS; Adam Green MD; Nitin Puri MD; Phil Dellinger MD, MCCM (SAGE Publishing, 2022)
Venovenous (VV) extracorporeal membrane oxygenation (ECMO) for severe acute respiratory distress syndrome (ARDS) is initiated in patients with high mortality as a potential lifesaving intervention. Hematologic malignancy (HM) is considered a relative exclusion criterion by the Extracorporeal Life Support Organization (ELSO). This case examines the relative contraindication and presents a successful outcome. A healthy 59-year-old male presented with respiratory distress. On arrival his S pO 2 on room air was 82%, chest x-ray revealed a lobar infiltrate, complete blood count demonstrated severe leukopenia, and a peripheral blood smear demonstrated cytoplasmic inclusions concerning for hairy cells. He was intubated and decision was made to initiate VV-ECMO during hospital day (HD) 1. Cytometry later confirmed a diagnosis of hairy cell leukemia (HCL). A diagnosis of Legionella was confirmed on HD 5. Initial hospitalization was complicated by progression to complete bilateral lung involvement, pulmonary hemorrhage, recurrent tachyarrhythmias, hemodynamic instability, and acute renal failure. Respiratory status stabilized and eventually began to improve. On HD 27, he was decannulated and later discharged to rehabilitation. Four months later he received inpatient chemotherapy and is currently in full remission. This is a successful outcome in a patient with severe ARDS requiring VV-ECMO in the setting of newly diagnosed HCL. The 10-year survival for treated HCL is near 100%. Due to favorable prognosis, HCL should not be considered a relative contraindication to VV-ECMO. While HM remains a relative exclusion criterion by the ELSO, it is important to analyze each patient individually and make decisions based on evolving bodies of evidence.